PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP KINERJA DI ASTON INN GIDEON BATAM - Ilham, Wahyudi (JURNAL SITEBA, 2023)
This research aims to investigate the influence of system quality and information quality on performance at Aston Inn Gideon Batam. This research employs a quantitative approach with data collection through questionnaires distributed to respondents directly involved in the use of information systems at Aston Inn Gideon Batam. The coefficient determination test results in this study reached 0.943 or 94.3%, indicating that the quality of the system and information variables contribute by 94.3% to employee performance at Hotel Aston Inn Gideon Batam. The multiple regression test results show a constant value of 1,900, indicating that if independent variables (X1 and X2) are constant, the employee performance value will be 1,900. The regression coefficient for system quality (X1) is 0.813, indicating that an increase of one unit in the system quality variable (X1) will increase employee performance (Y) by 0.499 units, meaning that higher system quality corresponds to higher employee performance. The regression coefficient for information quality (X2) is 0.665, indicating that an increase of one unit in the information quality variable (X2) will increase employee performance (Y) by 0.665 units. Simultaneous test results show an F value of 465.904 with a significance level of 0.000, which is less than 0.05. Therefore, F value > F table (465.904 > 3.11), indicating that collectively, the system quality and information quality variables have a positive and significant impact on employee performance.